Upaya Pemerintah Kampung dalam Pengembangan Bumk Sinar Jaya (Studi Pada Kampung Sinar Luas Kecamatan Bangun Rejo Kabupaten Lampung Tengah) - Sentia Febri; Yonna Wati; Tia Marlinda (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Palangka Raya, 2024)
The development of Village-Owned Enterprises (BUMK) is an important focus in the government's efforts to improve community welfare at the local level. In Sinar Luas Village, Central Lampung Regency, BUMK Sinar Jaya is one of the main initiatives in local economic development. However, the effectiveness of the village government's efforts in developing BUMK Sinar Jaya has not been fully revealed. This research aims to investigate the village government's efforts in developing BUMK Sinar Jaya in Sinar Luas Village, Bangun Rejo District, Central Lampung Regency. The main focus is to evaluate the strategies, policies and concrete steps taken by the village government to support the growth and sustainability of the BUMK. This research uses a qualitative approach by conducting a case study in Sinar Luas Village. Data was obtained through participatory observation, in-depth interviews with relevant stakeholders, and analysis of documents related to the development of BUMK Sinar Jaya. A triangulation approach was used to verify the validity of the data. The research results show that the village government has taken a number of efforts in developing BUMK Sinar Jaya, including outreach, training and providing supporting facilities. However, there are still obstacles related to the lack of community participation, technical problems in operations, and the need for increased coordination between village governments, BUMK managers, and the community.